The Relationship Between Criminal Law and Administrative Law in Crime Prevention - Huynh, Baokhanh Nguyen (Jurnal Cita Hukum, 2026)
In the context of increasing crime risks associated with socio-economic development and the expansion of state governance, crime prevention is increasingly seen as a comprehensive task of the legal system, rather than solely a function of criminal law. This article analyzes the relationship between criminal law and administrative law in crime prevention, approaching it from the perspective of risk management and early prevention. Based on a combination of criminal law theory, administrative law, and criminology, the article clarifies the preventive role of administrative responsibility, the position of criminal responsibility as a “last resort”, and the mechanisms of legal interoperability in controlling deviant behavior. Through an analysis of the provisions of the Vietnamese Criminal Code and the Law on Handling Administrative Violations, this article points out the theoretical and practical issues arising in determining the legal boundary between two types of responsibility, the risk of criminalizing administrative violations or administratively treating criminal acts. From there, the study proposes directions for improving the interconnected mechanism between criminal law and administrative law to enhance the effectiveness of crime prevention, while ensuring constitutional and legal principles and the control of state power.